DESIGN OF ADAPTIVE OVERCURRENT RELAY OF DISTRIBUTION SYSTEM WITH DISTRIBUTED GENERATION IN GRID-CONNECTED AND ISLANDED MODE - Sitorus, Ravendo
In recent times, the use of microgrid-based distributed generation with the application of renewable energy is considered to provide clean and efficient energy. However, the microgrid provides the possibility for distribution systems to operate in grid-connected or islanded. The use of distributed generation based on renewable energy provides a different short circuit current level when the distribution system operates in grid-connected or islanded. It causes the existing overcurrent protection to be not selective and fast in handling faults. This situation has an impact on increasing the likelihood of generation relays or relays far from the fault location are working first in clearing faults, with the result that will be a lot of loads that are not supplied by the generator, or the generator loses from the system. The main objective of this thesis is to design adaptive overcurrent protection, using load flow and short circuit simulation in both operating conditions, to obtain overcurrent relay settings. Load flow simulations were carried out using ETAP and short circuit simulations for several test buses were carried out using MATLAB / Simulink. The activation of the relay setting characteristics is updated through the status of the point of common coupling to determine whether the system is operation grid-connected or islanded. This research focuses on discussing the speed of inverse-time overcurrent protection through main protection and backup protection relays, with no other relay running faster. The simulation results in MATLAB / Simulink show that the relay settings designed to provide trip times in handled faults follow the applicable standards for main protection and backup protection relay.